COVID-19 and migration uncertainty in Kyrgyzstan: to leave or stay and earn? - Miholjcic, N. (University of London, 2021)
Kyrgyzstan is one of the most remittancedependent countries in the world.1 Remittance inflows to this low-income country have remained a key contributor to the country’s GDP over the past decade. Migration labor outflows continue to play a significant role in sustaining the Kyrgyz domestic economy. Due to the fact that Russia and the Central Asian region share a common history, cultural links, and lingua franca, the Russian market remains a popular destination for CA migrants.2 In 2019, almost 98% of Kyrgyz intra-family financial transfers came from the Russian Federation.3 However, the global coronavirus disease (COVID-19) pandemic has severely affected remittance flows to low and middle-income countries (LMICs) generally, and remittancedependent economies such as Kyrgyzstan have found themselves deeply vulnerable during different international events, including the financial crisis of 2008 and the current pandemic. To become more resilient, the Kyrgyzstan economy needs thorough reform that can improve the domestic job market and create more effective economic incentives that can decrease dependence on remittances and migration labor outflows, particularly in rural Kyrgyzstan.